Customer knowledge management via social media : the case of Starbucks - Chua, Alton Yeow Kuan (2013)
Purpose – The purpose of this paper is to analyze the extent to which the use of social media can support customer knowledge management (CKM) in organizations relying on a traditional bricks-and-mortar business model.